Marek’s Disease Virus (Gallid alphaherpesvirus 2)-Encoded miR-M2-5p Simultaneously Promotes Cell Proliferation and Suppresses Apoptosis Through RBM24 and MYOD1-Mediated Signaling Pathways - Zhu, Zhi-Jian; Teng, Man; Li, Hui-Zhen; Zheng, Lu-Ping; Liu, Jin-Ling; Chai, Shu-Jun; Yao, Yong-Xiu; Nair, Venugopal; Zhang, Gai-Ping; Luo, Jun (Frontiers in Microbiology, 2020)
MicroRNAs (miRNAs) have been demonstrated for their involvement in virus biology and pathogenesis, including functioning as key determinants of virally-induced cancers. As an important oncogenic α-herpesvirus affecting poultry health, Marek’s disease virus serotype 1 (Gallid alphaherpesvirus 2, GaHV-2) induces rapid-onset T-cell lymphomatous disease commonly referred to as Marek’s disease (MD), an excellent biological model for the study of virally-induced cancer in the natural hosts. Previously we have demonstrated that GaHV-2-encoded miRNAs (especially those within the Meq-cluster) have the potential to act as critical regulators of multiple processes such as virus replication, latency, pathogenesis and/or oncogenesis. In addition to miR-M4-5p (miR-155 homolog) and miR-M3-5p, we have recently found that miR-M2-5p possibly participate in inducing MD lymphomagenesis. Here we report the identification of two tumor suppressors, the RNA-binding protein 24 (RBM24) and myogenic differentiation 1 (MYOD1), being two biological targets for miR-M2-5p. Our experiments revealed that as a critical miRNA, miR-M2-5p promotes cell proliferation via regulating the RBM24-mediated p63 overexpression and MYOD1-mediated IGF2 signaling, and suppresses apoptosis by targeting the MYOD1-mediated Caspase-3 signaling pathway. Our data present a new strategy of a single viral miRNA exerting dual role to potentially participate in the virally-induced T-cell lymphomagenesis by simultaneously promoting the cell proliferation and suppressing apoptosis.